1988
DOI: 10.1515/bchm3.1988.369.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Active and Inactive Forms of Hemolysin (HlyA) fromEscherichia coli

Abstract: The HlyA protein (Mr 110 kDa) which is the gene product of the hlyA gene encoded by the hemolysin determinant of Escherichia coli (Goebel, W. & Hedgpeth, J. (1982) J. Bacteriol. 151, 1290-1298) was observed to accumulate in the culture supernatant (in the presence of the three other Hly proteins HlyC, B and D) throughout the active growth cycle. However, the amount of extracellular HlyA protein did not correlate with the external hemolytic activity, which declined when the cells entered the stationary phase. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 3 publications
5
26
0
Order By: Relevance
“…2. Only Wagner et al [20] have published cotnparable gels. This demonstrates the important point that a single 110 kDa polypeptide makes up for the protein moiety of haemolysin, as suggested by previous studies [6,21] but not by the data of Bohach and Snyder [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Only Wagner et al [20] have published cotnparable gels. This demonstrates the important point that a single 110 kDa polypeptide makes up for the protein moiety of haemolysin, as suggested by previous studies [6,21] but not by the data of Bohach and Snyder [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, this paper describes for the first time the inhibitory action of trypsin on an c<-haemolysin preparation whose protein component is only the 110 kDa polypeptide, thus relating directl~ this particular polypeptide to c~-haemolysin activity. The role of non-protein contponents in haemolytic activity, suggested by several workers [19,20] is not sufficiently documented as yet.…”
Section: Febs Iettersmentioning
confidence: 99%
“…3; Table 1). Because of the higher background activity associated with the hemolysin assay, it was not possible to determine whether LktC-activated AppA displayed a similar, low hemolytic activity (nonspecific lysis of erythrocytes by moderate amounts of cleared E. coli lysates has been previously reported [37]). Lysates from E. coli expressing lktA in the absence of RTX C gene function were found to exhibit leukotoxin activity which was low (1% of that observed with LktC activation) but reproducibly above background levels ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…HlyA is a protein of 110 kilodaltons which is hemolytically inactive in the absence of HlyC. The mechanism by which HlyC converts HlyA to a pore-forming cytolysin (10) is still unknown, but is has been shown that hemolytically active and inactive extracellular HlyA proteins differ in various properties (18). The specific hemolysin transport system consisting of at least the two membrane proteins HlyB and HlyD (19) allows the translocation of HlyA in the presence or absence of HlyC (11,12), indicating that HlyC is not essential for hemolysin transport.…”
mentioning
confidence: 99%